2012
DOI: 10.3389/fimmu.2012.00142
|View full text |Cite
|
Sign up to set email alerts
|

The role of Th cell subsets in the control of Helicobacter infections and in T cell-driven gastric immunopathology

Abstract: Chronic infection with the gastric bacterial pathogen Helicobacter pylori causes gastric adenocarcinoma in a particularly susceptible fraction of the infected population. The intestinal type of gastric cancer is preceded by a series of preneoplastic lesions that are of immunopathological origin, and that can be recapitulated by experimental infection of C57BL/6 mice with Helicobacter species. Several lines of evidence suggest that specific T cell subsets and/or their signature cytokines contribute to the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The major exception is H. felis for which experimental models of infection have existed since the early 1990's, and for which different mice strains have been well-established as models of chronic gastritis [86] , gastric atrophy [87][88][89] , gastric MALT lymphoma [60] , and gastric carcinoma [90,91] . Infection with H. felis in these models are often also used to study the pathogenesis of infection and the host immune response to H. pylori [92][93][94][95] . [63,[96][97][98][99] .…”
Section: Infectionsmentioning
confidence: 99%
“…The major exception is H. felis for which experimental models of infection have existed since the early 1990's, and for which different mice strains have been well-established as models of chronic gastritis [86] , gastric atrophy [87][88][89] , gastric MALT lymphoma [60] , and gastric carcinoma [90,91] . Infection with H. felis in these models are often also used to study the pathogenesis of infection and the host immune response to H. pylori [92][93][94][95] . [63,[96][97][98][99] .…”
Section: Infectionsmentioning
confidence: 99%
“…83 Not only can CagA induce cell scattering and elongation in a phosphorylation-dependent manner, CagA can also initiate this process in a phosphorylation independent the absence of the Th17 polarizing cytokine IL-23, IL-23p19 -/-mice exhibit significantly less gastritis and precancerous lesions, while IL-23 -/-H. pylori infected mice show decreased gastritis, decreases in the cytokines IL-17 and IFN-γ, and concomitant increases in bacterial burden. 58,59 IL-23 therefore appears to contribute to gastric pathology through activation of Th1/Th17 immune responses that control H. pylori infection by initiating inflammation and controlling the degree of gastritis. 58,59 The results from these animal experiments have also been extrapolated to human samples.…”
Section: Cagamentioning
confidence: 99%
“…58,59 IL-23 therefore appears to contribute to gastric pathology through activation of Th1/Th17 immune responses that control H. pylori infection by initiating inflammation and controlling the degree of gastritis. 58,59 The results from these animal experiments have also been extrapolated to human samples. Analysis of patients with a past, but not current, H. pylori infection shows persistent H. pylori specific Th17 responses.…”
Section: Cagamentioning
confidence: 99%
See 1 more Smart Citation
“…[2,7,8] Considerable studies have demonstrated that a mixed response of Th1 and Th17 cells plays a critical role in H. pylori-induced inflammatory gastric diseases and cancer. [9,10] The phenotypes of T helper subsets are determined by the local cytokine milieu and their lineage-specific transcription factors. [11][12][13] H. pylori elicits Th1 response to produce interferon-γ and tumor necrosis factor-α causing chronic gastritis and ulcers.…”
Section: Introductionmentioning
confidence: 99%